Penyuluhan Hukum Waris Sebagai Upaya Pencegahan Konflik Keluarga Pada Anggota Pengajian Medan Johor - Sherhan Sherhan; Parlindungan Purba; Dewi Ervina Suryani Sitorus (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Family conflicts triggered by inheritance distribution issues are a common phenomenon in society, primarily due to a lack of understanding of applicable inheritance laws, both according to Islamic law and positive law in Indonesia. This community service activity aims to provide inheritance law education to members of a religious study group in Medan Johor District as a preventative measure against potential family conflicts. Implementation methods included lectures, interactive discussions, and relevant case studies, with legal experts as resource persons. The results of the activity showed an increased understanding of the participants regarding the basic principles of inheritance law and the importance of open communication within families regarding the distribution of inheritance. This education is expected to be the first step in building legal awareness and realizing family harmony in the Medan Johor community.